2009
DOI: 10.1002/chem.200801458
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Structure Direction of Microporous Aluminophosphates: Competition between Organic Molecules and Water

Abstract: A combination of experimental characterisation techniques and computational modelling has allowed us to gain insight into the molecular features governing structure direction in the synthesis of microporous aluminophosphates. The occlusion of three different structure-directing agents (SDAs), triethylamine (TEA), benzylpyrrolidine (BP) and (S)-(-)-N-benzylpyrrolidine-2-methanol (BPM), within the AFI structure during its crystallisation, together with the simultaneous incorporation of water, has been experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…For studies of the structure‐directing factors, computational studies are usually employed to elucidate the role of the OSDAs . In some studies, a priori statistical calculus was also performed to find the best synthesis conditions to obtain the most crystalline zeolite, but what if these calculi were used to understand the factors that drive the formation of a certain zeolitic phase?…”
Section: Introductionmentioning
confidence: 99%
“…For studies of the structure‐directing factors, computational studies are usually employed to elucidate the role of the OSDAs . In some studies, a priori statistical calculus was also performed to find the best synthesis conditions to obtain the most crystalline zeolite, but what if these calculi were used to understand the factors that drive the formation of a certain zeolitic phase?…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Recently, through computational methods it has been shown that water molecules reside in the 6-membered ring channels or, with the organic template, in the 12-membered ring channels pointing in the same direction as crystal growth, the c direction. 32 Therefore, this increase in the c parameter, over crystallization time, could be due to the uptake of water molecules which may coordinate to Al(III) ions accessible in the channel direction, increasing the Al-O bond distance from 1.74 Å for tetrahedral Al(III) up to 1.9 Å for an octahedral environment; the more hydrophilic pure AlPO-5 material would therefore show a larger increase in the c parameter compared to MeAlPO-5. It should be noted that template orientation within the structure could also play a role in this change in c parameter and cell volume.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have demonstrated the important role that water molecules play, in addition to the organic SDA molecules, in the energy balance and in the structure directing effect of the AFI structure. 14 In addition, the energetics involved in the H-bond network formation of water clusters embedded within nanoporous aluminophosphates, leading to a clear structural relationship between the framework and the water cluster, and its role on the material formation have been recently addressed. 15 Previous works carried out in our laboratories showed the high structure directing activity of benzylpyrrolidine (BP) and (S)-(-)-N-benzylpyrrolidine-2-methanol (BPM) in the synthesis of the AFI structure.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed a computational methodology that permits to study the energetic effect of water in the synthesis of nanoporous structures; both cooperative and competitive water/SDA effects can be described in the model, which has been successfully applied to study structure direction to the AFI topology. 14 However, the AFI structure is a relatively simple structure in terms of topological features, since it contains only one-dimensional not-interconnected 12 MR channels; we now apply our computational model to the more complex SAO framework to test its validity and predictive ability. In this work, we employ the same computational methodology described in ref 14 to study the occlusion of the two SDA molecules (BP and BPM) and water within the SAO framework, and compare the computational results with experimental data.…”
Section: Introductionmentioning
confidence: 99%